2007
DOI: 10.1021/jp074884l
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Packing in Amorphous Carbohydrate Matrixes

Abstract: The molecular packing of bidisperse matrixes of amorphous carbohydrates consisting of a fractionated maltopolymer supplemented with various amounts of the disaccharide maltose is investigated by combining Positron Annihilation Lifetime Spectroscopy (PALS) with specific volume measurements. The maltopolymer-maltose blends are equilibrated at a range of water activities between 0 and 0.75 at 25 degrees C in order to investigate the effect of water content and carbohydrate molecular weight distribution on the siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
94
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(107 citation statements)
references
References 25 publications
10
94
0
3
Order By: Relevance
“…As discussed above, the average hole size increases linearly with τ o-Ps . The values presented in the present study are similar to values obtained in the literature 29 . Although the difference within the measured series of samples was small, it is still significant with respect to lipid oxidation especially when taking into consideration that the diffusivity is exponentially related to the radius of the free volume elements.…”
Section: Resultssupporting
confidence: 92%
“…As discussed above, the average hole size increases linearly with τ o-Ps . The values presented in the present study are similar to values obtained in the literature 29 . Although the difference within the measured series of samples was small, it is still significant with respect to lipid oxidation especially when taking into consideration that the diffusivity is exponentially related to the radius of the free volume elements.…”
Section: Resultssupporting
confidence: 92%
“…dextrans) may also have biopreserving effects because of their high Tg, despite their lower ability to interact directly with protein or membrane surfaces [26]. They are indeed largely excluded from the biomolecule surface, because of their large free volumes and steric hindrance [56,57]. In this respect, it is to be observed that the basic working mechanism of polymeric sugars is more or less the same as that of all the high molecular components in vivo, i.e.…”
Section: Disaccharides and Polysaccharides: Specific Vs Aspecific Matmentioning
confidence: 99%
“…In this case, the solvent appears like a porous medium where smaller biomolecules can diffuse, despite the high viscosity of the solution [63]. In this scenario, mono-or disaccharides could synergistically contribute to bioprotection, because they can settle in the oligosaccharide matrix, enhancing the matrix capability to interact with embedded structures [57,64]. Actually, disaccharides combined with long chain maltopolymers (e.g., maltodextrin or starch) are widespread as glass formers in food industry.…”
Section: Disaccharides and Polysaccharides: Specific Vs Aspecific Matmentioning
confidence: 99%
“…[1012, 21,22]. In addition, plasticisation is commonly accompanied by a signicant increase in the diusional mobility of small molecules (e.g.…”
Section: It Is Clear Frommentioning
confidence: 99%